Establishing Reference Intervals for Bone Turnover Markers in the Healthy Shanghai Population and the Relationship with Bone Mineral Density in Postmenopausal Women - Wei-Wei Hu; Zeng Zhang; Jin-Wei He; Wen-Zhen Fu; Chun Wang; Hao Zhang; Hua Yue; Jie-Mei Gu; Zhen-Lin Zhang (International Journal of Endocrinology)
The reference ranges of bone turnover markers (BTMs) were important during the treatment of osteoporosis, and the associations with bone mineral density (BMD) were controversial. The aim of this study was to establish the reference ranges of N-terminal procollagen of type l collagen (P1NP), osteocalcin (OC), and beta C-terminal cross-linked telopeptides of type I collagen (β-CTX) in Shanghai area and to investigate the relationships between BTMs and BMD in postmenopausal women. 2,799 subjects recruited in Shanghai City were measured BTMs to establish the reference ranges. Additional 520 healthy postmenopausal women were also measured BTMs, these women measured BMD in addition. BTMs were measured using the Roche electrochemiluminescence system. We used the age range of 35 to 45-year-olds to calculate reference intervals. The reference range of OC was 4.91 to 13.90 ng/mL for women and 5.58 to 16.57 ng/mL for men, P1NP was 13.72 to 32.90 ng/mL for women and 16.89 to 42.43 ng/mL for men, and β-CTX was 0.112 to 0.210 ng/mL for women and 0.100 to 0.378 ng/mL for men. BTMs significantly negatively correlated with lumbar spine and femoral and total hip in postmenopausal women ( = −0.157 ~ −0.217, P < 0.001). We established the normal reference ranges of P1NP, OC, and β-CTX in the Shanghai area. This study also found that BTMs correlated with BMD and suggested that BTMs were the key determining factors of early BMD decreases.